PENGARUH LIKUIDITAS DAN SOLVABILITAS TERHADAP PROFITABILITAS (Survei pada Sektor Industri Dasar dan Kimia Subsektor Semen yang Terdaftar di BEI Tahun 2012-2017) - Astrid Nurmayangsari (Scientia Regendi, 2021)
The purpose of this study is to determine the effect of Liquidity and Solvency on Profitabilitiy either simultaneously or partially. This research is conducted on Basic and Chemical Industry of Cement Subsector Registered in Indonesia Stock Exchange 2012-2017. The samples are obtained by purposive sampling, the samples were chosen with certain criterion, so that according to the research which is designed. The samples obtained in this study there are 3 companies per year. The analysis was performed using multiple linear regression with Path Analysis. The results of this study indicate that liquidity and solvency are at a significant level of “strong” relationship. Liquidity has no significant effect on profitability. Solvency has no significant effect on profitability. Liquidity and solvency simultaneously have a significant effect on profitability. Keywords : Liquidity, Solvency, and Profitability